ALGORITMA PERKALIAN TANGGA DAN APLIKASI BENTUK TRINOMIAL PADA PEMANGKATAN BILANGAN TIGA DIGIT - Jufri Jufri; Hera Deswita (RJOCS (Riau Journal of Computer Science), 2018)
This article discusses the generalization of multiplication staircase that originally applied to the binomial coefficients and coefficients trinomial. This generalization will form an algorithm. Furthermore, this article also discusses the application of trinomial forms in the appointment of three-digit numbers